Emerging Molecular and Biological Functions of MBD2, a Reader of DNA Methylation - Wood, Kathleen H.; Zhou, Zhaolan (Frontiers in Genetics, 2016)
DNA methylation is an epigenetic mark that is essential for many biological processes and is linked to diseases such as cancer. Methylation is usually associated with transcriptional silencing, but new research has challenged this model. Both transcriptional activation and repression have recently been found to be associated with DNA methylation in a context-specific manner. How DNA methylation patterns are interpreted into different functional output remains poorly understood. One mechanism involves the protein ‘readers’ of methylation, which includes the methyl-CpG binding domain (MBD) family of proteins. This review examines the molecular and biological functions of MBD2, which binds to CpG methylation and is an integral part of the nucleosome remodeling and histone deacetylation (NuRD) complex. MBD2 has been linked to immune system function and tumorigenesis, yet little is known about its functions in vivo. Recent studies have found the MBD2 protein is ubiquitously expressed, with relatively high levels in the lung, liver, and colon. Mbd2 null mice surprisingly show relatively mild phenotypes compared to mice with loss of function of other MBD proteins. This evidence has previously been interpreted as functional redundancy between the MBD proteins. Here, we examine and contextualize research that suggests MBD2 has unique properties and functions among the MBD proteins. These functions translate to recently described roles in the development and differentiation of multiple cell lineages, including pluripotent stem cells and various cell types of the immune system, as well as in tumorigenesis. We also consider possible models for the dynamic interactions between MBD2 and NuRD in different tissues in vivo. The functions of MBD2 may have direct therapeutic implications for several areas of human disease, including autoimmune conditions and cancer, in addition to providing insights into the actions of NuRD and chromatin regulation.